2012
DOI: 10.1159/000335411
|View full text |Cite
|
Sign up to set email alerts
|

A Program of Physical Rehabilitation during Hemodialysis Sessions Improves the Fitness of Dialysis Patients

Abstract: Aim: The aim of the present study was to evaluate the influence of cycle exercise during hemodialysis (HD) on patients’ physical proficiency, muscle strength, quality of life and selected laboratory parameters. Patients and Methods: In a group of 29 (15 female, 14 male) HD patients (age 64.2 ± 13.1 years), 3 months of cycle training during dialysis sessions was performed. The following data were analyzed: strength of lower extremities (six-minute walk test, isokinetic knee extension, flexion peak torque), nutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 33 publications
2
40
0
2
Order By: Relevance
“…The increase in quantity of muscle fibres, in particular type II A, increased activation of satellite cells, increased number of mitochondria and blood vessels have been proven [15][16][17][18].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The increase in quantity of muscle fibres, in particular type II A, increased activation of satellite cells, increased number of mitochondria and blood vessels have been proven [15][16][17][18].…”
Section: Introductionmentioning
confidence: 98%
“…Furthermore, it has a favourable effect on the increase in volume and ejection fraction of the heart, and on reduction in stiffness and resistance of blood vessels as well as on reduction in total and LDL cholesterol values. As a result, this is conducive to blood pressure normalization [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that L -carnitine [18,19,20,21,22,23], nandrolone decanoate [17] and growth hormone [24] supplementation may be useful. Some studies support the positive effects of regular physical activity on fatigue in patients on chronic hemodialysis [25,26,27]. …”
Section: Discussionmentioning
confidence: 99%
“…In other studies, physical inactivity has been shown to be associated with numerous clinical and laboratory variables such as insomnia, restless leg syndrome, depression [25], aging, diabetes and higher BMI [26], lower 25-OH vitamin D concentrations [27], parameters of malnutrition and/or chronic inflammation [28]. …”
Section: Discussionmentioning
confidence: 99%
“…The patients usually cycle for 10-45 min and progressively resistance is applied to the bicycle wheels [72][73][74][75][76][77][78][79][80][81][82]. Also, resistance exercises have been applied in intradialytic exercise training programs without serious complications and induced beneficial effects on patient's muscular strength [83][84][85][86][87][88][89][90] The exercises sessions occurred at the hemodialysis centers during the first two hours of the hemodialysis treatment (table 4).…”
Section: Effects Of Intradialytic Exercise Programsmentioning
confidence: 99%